2014
DOI: 10.1002/jsfa.6904
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of Cholestin on ethanol induced oxidative stress in rats

Abstract: Cholestin shows a protective effect against hepatotoxicity indices in ethanol-fed rats comparable to that of silymarin, as supported by the evaluation of liver histopathology. The data suggest that Cholestin exerts its hepatoprotective effect by decreasing lipid peroxidation and improving antioxidants status, thus proving itself as an effective antioxidant in ethanol-induced oxidative damage in rats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Because of varying hepatic cell damages, such as chronic alcohol intake, the levels of ALT and AST are elevated in the plasma. Thus, the increase in AST and ALT are often employed as indicators of cellular damages and hepatic functional impairments [36]. ALT and AST levels in ALD model significantly increased compared with control.…”
Section: Discussionmentioning
confidence: 99%
“…Because of varying hepatic cell damages, such as chronic alcohol intake, the levels of ALT and AST are elevated in the plasma. Thus, the increase in AST and ALT are often employed as indicators of cellular damages and hepatic functional impairments [36]. ALT and AST levels in ALD model significantly increased compared with control.…”
Section: Discussionmentioning
confidence: 99%
“…Serum AST, ALT, ALP, and LDH are among the most sensitive biochemical markers employed in the assessment of liver function. It is proved that AST, AST, ALP, and LDH can be expressed in the liver and that abnormal upregulation of these enzymes would cause damage and necrosis of hepatic cells [ 25 , 26 ]. When the permeability of hepatocellular membrane is enhanced under pathological conditions, these cellular enzymes are released into the bloodstream, resulting in an elevation of serum enzyme levels.…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, PD administration further augmented the activities of these two enzymes as compared with ethanol group. The enhancement of this compensatory mechanism by PD might contribute to its hepatoprotective effects by stimulating ethanol metabolism [ 26 , 38 ]. Additionally, our results also demonstrated that the increase of ALDH level was much more potent than that of the ADH level, suggesting that PD is able to avoid acetaldehyde accumulation.…”
Section: Discussionmentioning
confidence: 99%
“…AST and ALT are known as being reliable markers for hepatocyte injury liver function leading to necrosis (Ozer et al, 2008). Damaged hepatocytes release their contents into the extracellular space, and so, increased levels of AST and ALT in serum indicate increased permeability and damage and/or necrosis of hepatocytes (Hsieh et al, 2015;Ozer et al, 2008). AST and ALT activities in serum have been previously found to be increased due to ischaemia-reperfusion injury (Gonzalez-Flecha et al, 1993).…”
Section: Enzymatic Activities Of Liver Injury Biomarkers In Serummentioning
confidence: 99%